Pilot Study on Islamic Education Teachers' Perspectives on Mentoring Practices by the Head of the Islamic Education Panel and Their Impact on Teacher Quality - Kitikedizah, Hambali; Mohd Sham, Kamis; Maimun Aqsha Lubis, Abdin Lubis; Khadijah Abdul, Razak (Elite Scientific Publications, Pakistan, 2024)
This study investigates Islamic Education (IEC) teachers' views on the mentoring practices implemented by the Head of the Islamic Education Panel in schools and examines their relationship with the quality of IEC teachers. A pilot study was conducted with 33 IEC teachers in Sarawak, utilizing a research questionnaire comprising 29 items, administered online. Descriptive statistics—such as frequencies, mean scores, standard deviations, and percentages—were employed for data analysis. The findings revealed that both the perception scores of IEC teachers regarding mentoring practices and their overall impressions were modest. This underscores the crucial role the Head of the Islamic Education Panel plays in guiding IEC teachers within schools. The implications suggest that effective mentoring practices can significantly enhance the quality of IEC teachers, particularly in teaching and learning aspects.